Armut von Erwerbstätigen im europäischen Vergleich: eine Analyse unter Berücksichtigung des Einkommensverteilungsprozesses - Henning Lohmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
In Europe, there are significant differences in the extent and in the structure of in-work poverty. Based on a comparison of 20 countries the present study analyses to what extent this is due to the differences in the institutional framework conditions of a given country. The analy-ses are based on micro data from the EU Statistics on Income and Living Conditions (EU-SILC) of 2006 and macro data from different sources. The analyses distinguish between different steps in the process of income generation and redistribution. The starting point is the question whether a person's own income from work is sufficient to avoid poverty. Further steps regard the role of the household context (needs and further income) and the effect of state redistribution (taxes and transfers). This comprehensive perspective allows for a separation of labour market related and other influences on the risk of in-work poverty.
Keywords: 330; Poverty; employment; working poor; welfare state; Armut; Armutspolitik; Arbeitskräfte; Niedriglohn; Sozialtransfer; Sozialstaat; Einkommensverteilung; EU-Staaten